The effects of workforce diversity towards organizational creativity and the moderating role of knowledge sharing - Kanniaspran, Kannika; Mansor, Mohd Fitri; Mohd Kassim, Muhammad Asyraf (2018)
Workforce diversity is one of valuable asset for every business that seeks competitive advantage globally.Prior research found that advancement in workforce diversity enhance besides hindrance to organization performance.Deterioration to handle workforce diversity leads to organization collapse.In order to be successful, organization needs to effectively manage workforce diversity. This study, develops theoretical framework that extend prior research by explore how workforce diversity (functional background diversity, educational background diversity, organizational tenure diversity) and knowledge sharing influences organizational creativity.Main objective of the study advances by examining how workforce diversity affects organizational creativity.The specific objective of study analyze the effects of functional background diversity, educational level diversity, organizational tenure diversity) towards organizational creativity and the moderating role of knowledge sharing.Current study conducted to propose new theoretical framework on workforce diversity and organizational creativity. Findings of the study will propose a theoretical framework on the effects of workforce diversity towards organizational creativity and the moderating role of knowledge sharing.Again, findings of this study will help organizations and practitioners to effectively manage workforce diversity to gain organizational creativity as well as a basis for future research.This study addresses several research gaps by capture the complexity of dimension that lead to deep level diversity in group such as functional background diversity, educational background diversity, and organizational tenure diversity on organizational creativity.Also, the knowledge sharing moderates the relationship between workforce diversity and organizational creativity.This study makes contribution by highlighting the effective collaborated diversity variable in predicting expected result.